Effect of Ti2Ni/TiC ratios and sintering temperatures on the performance of TiC-TiNi cermets. (January 2023) - Shao, Yang; Ma, Haiwen; Yu, Weikang; Zhu, Wendi
Abstract: In this paper, TiC-TiNi cermets were prepared using brittle Ti2 Ni and TiC powders. The effect of mass ratios of Ti2 Ni/TiC and sintering temperatures on microstructures, martensitic transformation behaviors and mechanical properties of the cermets was investigated in detail. The results showed that ductile near-equiatomic TiNi could form due to interdiffusion between TiC and Ti2 Ni powders during sintering process. When mass ratio of Ti2 Ni/TiC was 1: 1, the cermets consisted of TiC, B2-TiNi and B19'-TiNi phases. While for cermets with mass ratio of Ti2 Ni/TiC larger than 1:1, Ti2 Ni phase appeared. The TEM, EDS and DSC results further confirmed that the presence of near-equiatomic TiNi formed after sintering at high temperatures. The TiC particles coarsened seriously with increasing sintering temperatures. The transverse strength increased firstly and then decreased with increasing sintering temperatures. The highest transverse strength reached 1117 MPa for the sample with Ti2 Ni/TiC = 1: 1 sintered at 1400 °C. The ductile near-equiatomic TiNi binder formed in the binder could effectively prevent crack propagations and increase toughness of the cermets during bending tests. Highlights: TiC-TiNi cermets were fabricated using brittle Ti2 Ni powders. Near-equiatomic TiNi binder formed after sintering at high temperatures. TiC-TiNi cermets exhibited a high transverse strength.